2022
DOI: 10.1155/2022/1445932
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis Reveals the Relation between TRMT112 and Tumor Microenvironment

Abstract: Dysregulated epigenetic modifications play a critical role in cancer development where TRMT112 is a member of the transfer RNA (tRNA) methyltransferase family. Till now, no studies have revealed the linkage between TRMT112 expression and diverse types of tumors. Based on TCGA data, we first probed into the relation between TRMT112 and prognosis and the potential role of TRMT112 in tumor microenvironment across 33 types of tumor. TRMT112 presented with increased expression in most cancers, which was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Bud23 is methylated by Trm112 in S. cerevisiae , while Trmt112, the methyltransferase homolog, carries out this reaction in humans. TRM112 and TRMT112 are AdoMet-dependent methyltransferases, which play a role in ribosome biogenesis and cell proliferation in both humans and S. cerevisiae , and have also been identified as being involved in tumor formation in humans ( Xu et al . 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bud23 is methylated by Trm112 in S. cerevisiae , while Trmt112, the methyltransferase homolog, carries out this reaction in humans. TRM112 and TRMT112 are AdoMet-dependent methyltransferases, which play a role in ribosome biogenesis and cell proliferation in both humans and S. cerevisiae , and have also been identified as being involved in tumor formation in humans ( Xu et al . 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… 42 TRMT112 not only participated in multiple biological processes, including cell proliferation and DNA damage, 43 but also exhibited positive correlation with various immune cells, such as dendritic cells, T cells and macrophages. 44 In summary, GMPI is likely to be a prognostic indicator to evaluate the aggressiveness and immune status of OC.…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, TRMT112 and WBSCR22 synergistically inhibit pancreatic cancer progression by repressing ISG15 transcription, which seems to support the possibility that TRMT112 is a tumor suppressor [ 106 ]. However, another report showed that TRMT112 was significantly upregulated in multiple cancers and was accompanied by a poorer prognosis [ 107 ]. Therefore, further validation is required to ascertain the involvement of TRMT112 and TRMT11/THUMPD2/THUMPD3 in the proliferation of diverse cancer cells.…”
Section: Trna Biological Functionmentioning
confidence: 99%